'IISR Thevam', 'IISR Malabar Excel' and 'IISR Girimunda'- three new black pepper (Piper nigrum L.) clones - K N Babu, B K Moorthy, B Sasikumar, P Haridas, J K George, K V Saji, T J Zachariah, P N Ravindran; Parthasarathy, P A Mathew, V A (Journal of Spices and Aromatic Crops, 2004)
Based on 7 years' performance at Valparai (Tamil Nadu) (3000 ft MSL), and 2 years' performance at Peruvannamuzhi (Kerala) and quality evaluation, three black pepper lines namely, Call. 1041, HP-813 and HP-I05 were superior and proposed for release as 'IISR Thevam', 'IISR Malabar Excel' and 'IISR Girimunda', respectively. These lines were superior to at least one of the controls for more than one character at one or both the locations. Trials laid out at farmers' fields in four northern districts of Kerala also indicated the superiority of these lines. Call. 1041 besides out-yielding control, exhibited a high degree of field tolerance to foot rot disease, whereas HP-813 had oleoresin content as high as 12%.